2017
DOI: 10.1021/acs.jpca.7b02580
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Hedgehoglike F-TiO2(B)/CNT Nanocomposites for Sonophotocatalytic and Photocatalytic Degradation of Malachite Green (MG) under Visible Light: Kinetic Study

Abstract: The present study describes the preparation of hedgehoglike F-doped titanium dioxide bronze (F-TiO(B)) and its nanocomposites containing single-walled and multiwalled carbon nanotubes (SWCNTs, MWCNTs) by using combined ball milling-hydrothermal processes. Then, sonophotocatalytic and photocatalytic degradation of malachite green (MG) dye from aqueous solution using prepared materials was performed. The results show that F-TiO(B)/SWCNT displays a good sonophotocatalytic and photocatalytic performance among othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(15 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…Similarly, the photoreactivity of F-doped TiO2 was improved after coupling with Bi2O3 to form a Bi2O3/F-doped TiO2 heterojunction [83]. Carbon nanotubes (CNTs) have also been used to modify F-doped TiO2, improving its photoreactivity by reducing the band gap from 3.02 to 2.7 eV and facilitating quick removal of the photo-generated electrons [84].…”
Section: Fluorine-doped Tio2 Heterojunctionsmentioning
confidence: 99%
“…Similarly, the photoreactivity of F-doped TiO2 was improved after coupling with Bi2O3 to form a Bi2O3/F-doped TiO2 heterojunction [83]. Carbon nanotubes (CNTs) have also been used to modify F-doped TiO2, improving its photoreactivity by reducing the band gap from 3.02 to 2.7 eV and facilitating quick removal of the photo-generated electrons [84].…”
Section: Fluorine-doped Tio2 Heterojunctionsmentioning
confidence: 99%
“…According to the discussions in Fiyadh et al (2019), functionalization of CNTs can be covalent and non-covalent, whereby the former class is when functional groups get attached by covalent forces to the skeletal structure of CNTs through chemical reaction, and the latter type of functionalization occurs when functional groups coat the CNTs walls (Karousis et al 2010). Xia et al (2007), Mamba et al (2015), Zouzelka et al (2016), Réti et al (2016) and Panahian and Arsalani (2017) have indicated that CNTs can be combined with TiO 2 to generate composite structures for subsequent use as photocatalysts. Based on data in the literature, besides providing for a large surface area support to the TiO 2 particles, CNTs equally significantly retard the recombination of electrons and holes (Zouzelka et al 2016;Karthika and Arumugam 2017;Natarajan et al 2017).…”
Section: Multiwalled Carbon Nanotubes-type Photocatalystsmentioning
confidence: 99%
“…It degrades malachite green dye ∼50% in 120 min of light irradiation. When compared with other metal oxides, it is found that undoped TiO 2 NPs and F doped TiO 2 NPs photocatalytically degraded 99.9 and 54.26% MG dye in 240 min and 120 min, respectively (Chen et al, 2007;Panahian and Arsalani, 2017). Sn doped TiO 2 has been reported degrading 85% MG in 340 min under light irradiation (Sayilkan et al, 2007), while SnO 2 NPs degraded 27% MG in 180 min under UV light irradiation (Kumar et al, 2016).…”
Section: Photocatalytic Dye Degradationmentioning
confidence: 97%